Small-molecule studies identify CDK8 as a regulator of IL-10 in myeloid cells - Johannessen, Liv (Nat Chem Biol, 2017)
Enhancing production of the anti-inflammatory cytokine interleukin-10 (IL-10) is a promising strategy to suppress pathogenic inflammation. To identify new mechanisms regulating IL-10 production, we conducted a phenotypic screen for small molecules that enhance IL-10 secretion from activated dendritic cells. Mechanism-of-action studies using a prioritized hit from the screen, BRD6989, identified the Mediator-associated kinase CDK8, and its paralog CDK19, as negative regulators of IL-10 production during innate immune activation. The ability of BRD6989 to upregulate IL-10 is recapitulated by multiple, structurally differentiated CDK8 and CDK19 inhibitors and requires an intact cyclin C–CDK8 complex. Using a highly parallel pathway reporter assay, we identified a role for enhanced AP-1 activity in IL-10 potentiation following CDK8 and CDK19 inhibition, an effect associated with reduced phosphorylation of a negative regulatory site on c-Jun. These findings identify a function for CDK8 and CDK19 in regulating innate immune activation and suggest that these kinases may warrant consideration as therapeutic targets for inflammatory disorders.